PENINGKATAN KAPASITAS PRODUKSI MELALUI PENERAPAN THEORY OF CONSTRAINT, PENJADWALAN MESIN PARALEL DAN BOTTLENECK SCHEDULING PADA PERUSAHAAN SHEET METAL WORK - Sonia Nur Indah Suci; Nora Azmi; Sumiharni Batubara (JURNAL TEKNIK INDUSTRI, 2013)
This study aims to increase the production capacity of the server rack 08U Type Double ASeriesWallmounted BRI on company X. Current production did not reached the expected target of117 units / week because of the bottleneck workstation. The study began by identifying the bottleneckworkstation using the Theory of Constraints (TOC). The result of identification process showed twobottleneck work stations, that are work station Punching and Ovencoating. The production capacitywas improved by performing the steps as follows: 1) Add 1 machine at punching station, 2) performjob scheduling on parallel machines at punching station using Short Processing Time (SPT) criteria;3) perform job sequencing on bending station using Weighted Shortest Processing Time (WSPT)criteria; 4 ) adds overtime at ovencoating stations, and 5) implementing bottleneck scheduling methodto sequence all jobs. The Results of this study showed that makespan was reduced by 12.03% andproduction capacity increased by 41.9% so that the production target of 117% can be achieved.